Hemoglobin e prevalence among ethnic groups residing in malaria-endemic areas of Northern Thailand and its lack of association with plasmodium falciparum invasion in vitro - Pathrapol Lithanatudom (2018)
© 2016 Lithanatudom et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in anymedium, provided the original author and source are credited. Hemoglobin E (HbE) is one of the most common hemoglobin variants caused by a mutation in the β-globin gene, and found at high frequencies in various Southeast Asian groups. We surveyed HbE prevalence among 8 ethnic groups residing in 5 villages selected for their high period malaria endemicity, and 5 for low endemicity in northern Thailand, in order to uncover factors which may affect genetic persistence of HbE in these groups.We found the overall HbE prevalence 6.7%, with differing frequencies from 0% in the Pwo Karen, the Lawa, and the Skaw Karen to 24% in the Mon. All HbE genes were heterozygous (AE). Differences in HbE prevalence among the studied ethnic groups indirectly documents that ancestries and evolutionary forces, such as drift and admixture, are the important factors in the persistence of HbE distribution in northern Thailand. Furthermore, the presence of HbE in groups of northern Thailand had no effect on the in vitro infectivity and proliferation of Plasmodium falciparum, nor the production of hemozoin, a heme crystal produced by malaria parasites, when compared to normal red-blood-cell controls. Our data may contribute to a better understanding on the persistence of HbE among ethnic groups and its association with malaria.